Exploring the physics of the accretion and jet in nearby narrow-line Seyfert 1 galaxies. Issue 1 (24th March 2018) - Yao, Su; Qiao, Erlin; Wu, Xue-Bing; You, B
Abstract: In this paper, we explore the physics of the accretion and jet in narrow-line Seyfert 1 (NLS1) galaxy. Specifically, we compile a sample composed of 16 nearby NLS1 with L bol / L Edd ≳ 0.1. We investigate the mutual correlation between their radio luminosity L R, X-ray luminosity L X, optical luminosity L 5100, and black hole mass M BH . By adopting partial correlation analysis, we find (1) a positive correlation between L X and M BH and (2) a weak positive correlation between L R and L 5100 . However, we don't find significant correlations between L R and L X or between L X and L 5100 after considering the effect of the black hole mass, which leads to a finding that L X / L Edd is independent of L 5100 / L Edd . Interestingly, the findings that L X is correlated with M BH and L X / L Edd is not correlated with L 5100 / L Edd support that the X-ray emission is saturated with increasing $\dot{M}$ for L bol / L Edd ≳ 0.1 in NLS1, which may be understood in the framework of slim disc scenario. Finally, we suggest that a larger NLS1 sample with high-quality radio and X-ray data is needed to further confirm this result in the future.